2020
DOI: 10.1001/jamanetworkopen.2020.17859
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of Hyponatremia in Patients With Indwelling Peritoneal Catheters for Drainage of Malignant Ascites

Abstract: Key Points Question What is the incidence of hyponatremia after the placement of an indwelling peritoneal catheter for malignant ascites? Findings In this cohort study of 309 patients, the overall incidence of hyponatremia after the placement of an indwelling peritoneal catheter was 84.8%, yet hyponatremia was often untreated or unrecognized. Patients with hyponatremia prior to the placement of an indwelling peritoneal catheter and those with hepatopancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, there are currently no studies that investigated the safety of ascites removal in a daily manner. Another study also reported a high hyponatraemia incidence of almost 85% in patients with PeCa and malignant ascites 34 . Ascites sodium levels are often comparable to serum sodium levels and removing 1litre of ascites at a sodium level of 135 mmoL/L results in a total sodium loss of over 3 g/L.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, there are currently no studies that investigated the safety of ascites removal in a daily manner. Another study also reported a high hyponatraemia incidence of almost 85% in patients with PeCa and malignant ascites 34 . Ascites sodium levels are often comparable to serum sodium levels and removing 1litre of ascites at a sodium level of 135 mmoL/L results in a total sodium loss of over 3 g/L.…”
Section: Discussionmentioning
confidence: 92%
“…Another study also reported a high hyponatraemia incidence of almost 85% in patients with PeCa and malignant ascites. 34 Ascites sodium levels are often comparable to serum sodium levels and removing 1litre of ascites at a sodium level of 135 mmoL/L results in a total sodium loss of over 3 g/L. Daily removal of larger quantities of ascites could therefore trigger an absolute hyponatraemia.…”
Section: Discussionmentioning
confidence: 99%
“…Salt restriction of 2 to 3 g/d is recommended in individuals with ascites . However, device-associated desalination has been described in patients with malignant neoplasm–related ascites and patients present with (intravasal) hypovolemic hyponatremia . Since ascites and serum contain similar amounts of sodium, drainage of 1.5 L/d or more leads to a sodium loss of more than 4.5 g/d, if the serum sodium is higher than 135 mmol/L .…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia is another possible complication of prolonged MA drainage, however it may not have clinical signi cance, because it is often untreated or unrecognized. Nevertheless, a risk group of patients with hepatopancreatobiliary malignancy and hyponatremia before drainage was suggested for routine testing of plasma sodium concentration, because hyponatremia may have signi cant negative implications [22]. In another study sodium values declined both pre-and post-procedure (tunneled catheter insertion followed by drainage); the slope of decline diminished postprocedure compared with pre-procedure (sodium slope [-2.50 to 1.31 mEq/L, p = 0.037]).…”
Section: Safetymentioning
confidence: 99%